Ethnic conflict, civil war and cost of conflict - Caruso, R. (Contributions to conflict management, peace economics and development ;, 2011)
This volume of Contributions to Conflict Management, Peace Economics and Development includes some of the selected papers presented by scholars in a European Peace Science Network Meeting recently held in Amsterdam, The Netherlands. Chapters in this volume cover the conflicts in Maoist India, South America, and Sub-Saharan Africa. The authors have employed highly sophisticated quantitative techniques and principles of Economics and Political Science in determining the causes of these ethnic conflicts and effects on human and material resources.